1987
DOI: 10.1002/polb.1987.090250507
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic mechanical properties of homogeneous copolymers of ethylene and 1‐alkenes

Abstract: The dynamic mechanical properties of homogeneous copolymers of ethylene with 1‐butene, 1‐octene, and 1‐octadecene prepared by means of a vanadium‐based catalyst system have been determined. The 1‐butene copolymers show α′ and α transitions in the 20–60°C temperature range, whereas the 1‐octene and 1‐octadecene copolymers show single α transitions. The intensity of the β transition increases with comonomer content in 1‐butene and 1‐octene copolymers and also with the amount of interfacial material present. In e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 18 publications
5
31
0
Order By: Relevance
“…Also, it is possible that long branches can crystallize, forming crystallites with different sizes when compared with the main crystallizable chain. 17 In the case of ethylene/1-octadecene copolymers, several DSC thermograms exhibit the presence of more than one endotherm, indicating that the copolymers have more than one melting temperature (Table I). This behavior has been observed, especially for the copolymer with 5.1% of 1-octadecene and indicates the presence of crystals with different sizes.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…Also, it is possible that long branches can crystallize, forming crystallites with different sizes when compared with the main crystallizable chain. 17 In the case of ethylene/1-octadecene copolymers, several DSC thermograms exhibit the presence of more than one endotherm, indicating that the copolymers have more than one melting temperature (Table I). This behavior has been observed, especially for the copolymer with 5.1% of 1-octadecene and indicates the presence of crystals with different sizes.…”
Section: Methodsmentioning
confidence: 97%
“…[2][3][4] It is known that copolymers of ethylene and ␣-olefins with long chains, such as 1-octadecene, might show a different behavior from that usually found for ethylene/short ␣-olefins copolymers. 7,17 It is accepted that long branches may participate in the crystallization process, favoring the crystallinity. Also, it is possible that long branches can crystallize, forming crystallites with different sizes when compared with the main crystallizable chain.…”
Section: Methodsmentioning
confidence: 99%
“…Clas et al 17 observed also by DMA a deviating behavior between homogeneous ethene-butene, ethene-octene, and ethene-octadecene copolymers synthesized with vanadium catalysts: The intensity of the b transition increased with the comonomer content in 1-butene and 1-octene copolymers and also with the amount of interfacial material present. In ethene-1-octadecene copolymers, this intensity was comparatively low, even though there was about 20% interfacial material present.…”
Section: Dmamentioning
confidence: 98%
“…The influence of the structure and morphology on the dynamic mechanical behavior of PEs has been discussed in a number of publications, [11][12][13][14][15][16][17] An understanding of the principles involved is of value in predicting the response of these polymers in various product applications. In general, linear and branched PEs exhibit up to three transitions, which are labeled a, b, and c in order of decreasing temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Three relaxation processes of PE have been extensively studied. [21][22][23] It is generally considered that the ␤ (ϳ Ϫ20°C) and ␥-transitions (ϳ Ϫ120°C) are due to the motion of branches 24 -27 and to the crankshaft motion of short polymer segments requiring a minimum of three methylene units 23,[27][28][29] in the amorphous matrix, respectively. In contrast, the ␣-transition (ϳ 45°C) is attributed to motions or deformations in the interfacial region (tie molecules loops, folds, etc.…”
Section: Ultradrawing Of Gel Films Of Uhmwpe and Lmwpe Blendsmentioning
confidence: 99%